Risk of target non-attainment in obese compared to non-obese patients in calculated linezolid therapy. (September 2020) - Ehmann, L.; Simon, P.; Busse, D.; Petroff, D.; Dorn, C.; Huisinga, W.; Dietrich, A.; Zeitlinger, M.; Wrigge, H.; Kloft, C.
Abstract: Objectives: The aim was to characterize linezolid population pharmacokinetics in plasma and interstitial space fluid of subcutaneous adipose tissue (target site) of obese compared with non-obese patients and to determine dosing regimens enabling adequate therapy using Monte Carlo simulations. Methods: In this prospective, parallel group, open-label, controlled, single-centre trial, 30 surgery patients (15 obese, 15 non-obese) received 600 mg of intravenous linezolid. A population pharmacokinetic analysis characterizing plasma and microdialysis-derived target site pharmacokinetics was followed by Monte Carlo simulations using twice/thrice daily 600–1200 mg short-term and extended infusions of linezolid. Adequacy of therapy was assessed by the probability of pharmacokinetic/pharmacodynamic target attainment for time and exposure-related indices. Results: In the model, lean body weight and obesity status largely explained between-patient variability in linezolid PK parameters (12.0–44.9%). Both factors caused lower area under the concentration–time curve in typical obese patients in plasma (–20.4%, 95% CI –22.0% to –15.9%) and at target-site (–37.7%, 95% CI –47.1% to –24.2%) compared with non-obese patients. Probability of target attainment showed improvement with increasing linezolid doses. Depending on lean body weight, adequate therapy was partially attained for 900- and 1200-mg linezolid doses and minimum inhibitory concentrations (MICs) ≤2 mg/L (probability of target attainment 62.5–100%) but could not be reached for MIC = 4 mg/L (probability of target attainment ≤82.3%). Additionally, lower linezolid distribution into the target site in obese patients as described above might compromise the plasma-based probability of target attainment analysis. Discussion: This analysis revealed risks of linezolid underdosing in empirical antibiotic therapy of most resistant bacteria for obese and non-obese patients. Doubling the standard dose is associated with adequate probability of target attainment throughout most body masses for MIC ≤2 mg/L. Further clinical studies with adjusted dosing regimens in for example intensive care patients are needed.